Three Months of Composting Are Enough to Eliminate the Fowl Typhoid Bacteria - Campos, I. C. [UNESP]; Rodrigues Alves, L. B. [UNESP]; Saraiva, Mauro de Mesquita Souza [UNESP]; Lima, T. S. [UNESP]; Ferreira, V. A. [UNESP]; Ferreira, T. S. [UNESP]; Viana, G. B. [UNESP]; Almeida, A. M. [UNESP]; Rubio, M. S. [UNESP]; Berchieri, A. [UNESP] (FapUNIFESP (SciELO), 2023)
The composting technique has been increasingly highlighted in poultry production units, as an efficient and low-cost solution for the destination of carcasses. The process is based on the accelerated decomposition of organic material under high temperatures, associated with eliminating pathogenic microorganisms. This study aims to evaluate the effectiveness and the time necessary for the elimination of Salmonella Gallinarum in carcasses of poultry submitted to the composting process. The composting was carried out following the models used in the field, and microbiological analysis was performed in five different periods: 45, 90, 120, 150 and 180-days after closing the composter. After 90 days of experiment and in the subsequent analysis, the elimination of the bacteria in 100% of the samples was verified, validating the composting process as an effective method for eliminating S. Gallinarum in poultry carcasses, when respecting the period necessary for the elimination of the bacteria and the good quality of the structure adopted for the process.
Keywords: Avian salmonellosis; carcass slurry; poultry farm; Salmonella Gallinarum